2007 Electrical Insulation Conference and Electrical Manufacturing Expo 2007
DOI: 10.1109/eeic.2007.4562602
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature and thermal expansion on slot partial discharge activity

Abstract: The influence of generator load changes on partial discharge (PD) activity can be significant especially when the semi-conductive coating of stator bars is eroded. It is common knowledge that thermal expansion (copper, core and insulation) wiD decrease the gap size in the slot between the bar and the core and this could lead to a reduction of slot PD activity. In the present study, a surface defect was made on a stator bar and a variable gap between the bare insulation surface and a ground plane was adjusted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 7 publications
1
2
0
1
Order By: Relevance
“…This confirms that temperature is a major contributor in the slot PD process. This behavior is consistent with results of previous findings where the slot PD activity always increased proportionally with temperature [27,31]. Thus, both temperature and surface degradation play a role in the evolution of slot PDs over time.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This confirms that temperature is a major contributor in the slot PD process. This behavior is consistent with results of previous findings where the slot PD activity always increased proportionally with temperature [27,31]. Thus, both temperature and surface degradation play a role in the evolution of slot PDs over time.…”
Section: Discussionsupporting
confidence: 93%
“…Because of the heat, the insulation surfaces showed signs of thermal aging with changes in the color of the insulation. Previous work has revealed that an increase in temperature always leads to an increase in slot PD activity for short-term exposure [27]. Here, neglecting the influence of surface deposit, the sustained high energy of the PDs combined with the formation of ozone, which is a strong oxidizing agent, contributed to erode the insulation surfaces by degrading the organic compound of the epoxy resin and laterally damage the semi-conductive coating, extending the bare insulation area exposed to high voltage.…”
Section: Discussionmentioning
confidence: 96%
“…Esta irrupción vino de la mano de un corte de nudo gordiano respecto de los proyectos previos, los cuales quedaron de nuevo pospuestos en virtud de la sistematización de los manuscritos, en los que colaboraron Fink y Langrebe. 71 Husserl comentó a D. Cairns en 1931 que había pensado erróneamente que componer una introducción a la fenomenología para una audiencia amplia era algo simple, pero luego vio que sus intentos de los últimos diez años, en el arco que va desde las lecciones de Londres a las de Paris y sus rediseños, carecieron todos de resultados satisfactorios. 72 Husserl nunca concluyó el proyecto de la versión alemana, al que se refirió en 1930 como "el trabajo principal de mi vida", 73 pero sabemos que no mantuvo las energías en ese proyecto y, por el contrario, se orientó hacia los trabajos también inconclusos que conformaron luego el texto de la Crisis.…”
Section: Las Meditaciones Cartesianas Y La Pervivencia De Lo Momentáneounclassified
“…In the first case, purely electrical slot PD are expected to progress much more slowly than when the degradation is accelerated by mechanical vibrations. Furthermore, degradation is expected to be faster at temperatures higher than room temperature, since an increase in temperature is usually expected to lead to an increase in the slot PD activity [3]. While the influence of these stresses is generally accepted, the resulting differences in the evolution of the PD patterns are much less understood.…”
Section: Introductionmentioning
confidence: 98%